Solute carrier family 1 member 1 in renal interstitial fibrosis: evaluating its influence on glutamate uptake and extracellular ion levels - Lv, Chun Yan; Cheng, Xian Kui; Luo, Sen Fang; Yang, Wen Xuan; Liu, Geng Lin; Huang, Ting Ting; Chen, Shi Gao (Frontiers in Medicine, 2025)
GoalThis research sought to examine the role of solute carrier family 1 member 1 (SLC1A1) in renal interstitial fibrosis (RIF), exploring its relationship with fibrosis extent and its influence on amino acids absorption and ion levels.ApproachRenal tubulointerstitial damage was assessed using tissue microarray analysis combined with HE staining. Immunohistochemistry was used to identify SLC1A1 expression in fibrotic tissues, and its relationship with renal tubulointerstitial damage was examined. Additionally, an in vitro fibrosis model was created using HK-2 cells stimulated by transforming growth factor-β1 (TGF-β1). The levels of SLC1A1 protein were evaluated by immunofluorescence staining, while glutamate uptake capacity and extracellular ion and amino acid levels were monitored.FindingThe expression of SLC1A1 decreases in cases of renal interstitial fibrosis, with a more pronounced reduction as fibrosis worsens. Following 48 h of exposure to TGF-β1 (15 ng/mL), these alterations became even more apparent. At this 48 h mark, the glutamate uptake in the experimental group was significantly lower compared to the control group, while the levels of extracellular Na+ and Cl− showed a notable increase. Additionally, aspartic acid (ASP) levels rose, whereas glutamic acid (Glu) levels fell, and cysteine (Cys) levels remained unchanged.ConclusionThe downregulation of SLC1A1 during renal interstitial fibrosis is inversely related to the severity of fibrosis and impacts both glutamate uptake and the balance of extracellular ions, indicating its potential as a therapeutic target for enhancing kidney function.